The Ability of Pancasila and Civics Education Teachers in Implementing the Independent Learning Curriculum at SMA Negeri 2 Gunungsitoli in the 20222023 Academic Year - Syukur Niatman Harefa; Fatiani Lase (Universitas Muhammadiyah Enrekang, 2023)
This study aims to determine how the ability of ppkn teachers in implementing an independent learning curriculum, the obstacles faced by ppkn teachers in implementing an independent learning curriculum and to find out the efforts made by ppkn teachers in overcoming the obstacles to implementing an independent learning curriculum at SMA Negeri 2 Gunungsitoli in the 2022/2023 academic year. This research uses a descriptive approach with qualitative methods. The purpose of using a descriptive approach is to find meaning starting from facts by making observations recording all facts in a holistic scientific manner with the problems observed. The research instrument used in this research is the researcher himself by using a cellphone as a tool to record all conversations, pictures as real evidence, and a notebook that serves to record conversations with data sources or informants. The data collection techniques used were observation, interviews and documentation. The results of the research and discussion concluded that: First, the ability of Civics Teachers in implementing the Independent Learning Curriculum at SMA Negeri 2 Gunungitoli is the ability to manage independent learning, the ability to use varied and diverse learning methods and strategies, the ability to identify students' interests and needs, the ability to assist and guide students and the ability to manage classes. Second, the obstacles faced by Civics Teachers in implementing the Merdeka Belajar Curriculum are that teachers and students' understanding of the concepts and principles of the independent learning curriculum is still limited, the necessary resources are still very limited and minimal, including teaching materials such as incomplete textbooks, formative and authentic assessments. Third, the efforts made by Civics Teachers in overcoming obstacles are by participating in various trainings, webinars, and workshops organized by schools and the government regarding the implementation of the independent learning curriculum, utilizing the internet to find learning resources, evaluating and adjusting the learning strategies used to be in accordance with the principles of the independent learning curriculum.